An exploration of road-transport collaboration between private transport providers and humanitarian organisations through strategic CSI : A case-based approach - Potgieter, Daniella Nicola (Stellenbosch : Stellenbosch University, 2017)
Thesis (MCom)--Stellenbosch University, 2017.